The Effect of Project Based Learning in Realizing Performing Arts on Entrepreneurial Motivation in Art Learning in Vocational School Students - Anggraeni, Reni; Juju Masunah; Trianti Nugraheni (Mudra Jurnal Seni Budaya, 2024)
The competence that must be possessed by Vocational School (VS) students is to be able to find business opportunities independently. Related to the subjects of art and culture, it is hoped that VS students have the motivation that can be carried out by the presence of performing arts in the form of performances that can be used as opportunities for entrepreneurship. Thus, VS students must have entrepreneurial motivation to have business opportunities in the arts and culture sector. One of the learning strategies that can be used is to use PBL. PBL can increase students' learning motivation and also facilitate students' problem-solving abilities. This study aimed to determine how the implementation of PBL in realizing performances and the influence of PBL on entrepreneurial motivation in art learning for VS students. The research method uses an experimental research method with a one-group pretest-posttest design. Participants in this study were 37 students in one of the VS in the Indramayu district, and the study was conducted using a systematic sampling technique. The research instrument used an entrepreneurial motivation questionnaire. Data analysis techniques using statistical descriptions and Paired-Sample T-Test. This study concludes that PBL affects VS students' entrepreneurial motivation in art learning. PBL can motivate students to reflect on what they learn in an actual project and provide opportunities for students to think and be creative when realizing a project in the arts and culture. Students can understand that in the performance, various job descriptions can be used for business opportunities or jobs in arts and culture to conduct further research with more participants so that the results of this study can be more generalized.